PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI DAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris Pada OPD Kota Dumai) - Edlin, Debby Nadya; Taufik, Taufeni; Anisma, Yuneita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this study is to determine the effect of Capacity Human Resources, Utilization of Information Technology and Government Internal Control System on Quality ofFinancial Statements with Organizational commitment as Moderating VariableEmpirical Study at Dumai City Regency Regional Device Organization. The data used in this study is the primary data. The population in this research is all OPD officer of Dumai City. The sample in this study were 81 people selected by using purposive sampling. The analysis in this study was conducted using WarpPLS 5.0. The results of this study indicate that the Capacity Human Resources and Utilization of Information Technology affect the Quality ofFinancial Statementswhile the Government Internal Control System do not onQuality ofFinancial Statements. The Organizational commitment moderates the relationship between the Capacity Human Resources and Utilization of Information Technologyon the Quality ofFinancial Statements. However, the Organizational commitment does not moderate the relationship between the presentation of Government Internal Control Systemon the Quality ofFinancial Statements.Keywords : Capacity Human Resources, Utilization of Information Technology, Government Internal Control System, Quality ofFinancial Statements, Organizational commitment